Study of The Hepatorenal toxic effect of indomethacin and evaluation of the protective effect of aloe vera gel extract - حسن غادة; نهلة إبراهيم; عقيل حجوز; رنا عيسى (Latakia University Journal -Biological Sciences Series, 2025)
This study aimed to determine the effect of Ethanolic Aloe vera gel extract in alleviating or preventing the hepatotoxic and renal toxic effects induced by indomethacin in male albino mice, Thus, it can be adopted as a plant-based protective agent against the side effects of this drug. This study, included 30 white mice, (Balb/c strain), which were divided into three experimental groups (10 mice in each). as follows: The first group (the physiological control), was treated with oral cavity of DMSO 10% until the end of the experiment, while the second group (the pathological control), was treated with oral cavity of indomethacin in a single dose for 6 hours To induce toxicity ,whereas the third group (Protective) was treated with oral cavity of Ethanolic extract of Aloe vera gel for 30 days, then at the next day mice were treated with oral cavity of indomethacin in a single dose 166 mg⁄kg for 6 hours day . At the end of the experiment, the treated animals were anesthetized by Chloroform and dissected to obtain kidneys and livers. Histopathology results showed a toxic effect of indomethacin, represented by severe cytoplasmic necrosis and individual necrosis in some hepatic cells, In addition to severe vascular congestion, As for Renally with glomerular degeneration, vascular congestion, in addition to degenerative changes in the proximal tubules. Aloe vera gel extract showed an important protective effect, as it preserved the integrity of the hepatic tissue structure, with the exception of noting punctate lymphocytic infiltrates within the portal spaces and central vein congestion. Likewise, in the kidneys, it preserved the renal tissue structure, only vascular congestion was observed without any inflammatory infiltrates, which indicates its great effectiveness in scavenging free radicals and antioxidant.